Effect of Stress on Teachers’ Performance with Special Reference to Jaffna District Schools - Anandasayanan, S.; Subramaniam, V.A. (University of Sairam, 2013)
Stress is an unavoidable and dreaded, yet needed, part of everyday life. Although life’s stressors are usually thought of as only damaging to physical and mental health , they also motivate people to live actively and productively. Teaching is becoming more challenging as a profession and it is one of the most significant and visible profession in the world. Schools are as important as any other organization in the world. These are tough times to be a teacher. Main objective of this study is to identify sources of work stress in school teachers. Work Stress Questionnaire by Jaws was adapted to collect data. Random sampling was used to gather the responses of teachers from schools in Jaffna District. Multiple regression was used to find out the impact on the performance of teachers. The stress of the teachers is measured in the questionnaire based on the factors Such as Time Management , Work Related stressors , Professional distress, Discipline of the students and Professional investments. The finding of this study is teachers’ stress significantly impact on the performance of them.
Keywords: Time Management; Work Related stressors; Professional investments; Professional distress